Grondbezit in het Seleucidische Rijk - van der Spek, Robartus Johannes (1986)
Асаdemisch Proefschrift ter verkrijging van de graad van Doctor in de Letteren aan de Vrije Universiteit te Amsterdam; Promotores: P. W. de Neeve, M. Stol. Referenten: H. W. Pieket, G. van Driel; in Dutch; 249-256 English Summary: 1. Introduction; 2. The Concept of Ownership in Babylonian and Greek Law; 3. Land Tenure in Babylonia; 4. Land Tenure in more Hellenised Parts of the Empire; 5. Conclusion. 183-248: 11 LB texts are re-edited in transliteration, translation and with commentary